A randomised controlled trial of an advance care planning intervention for patients with incurable cancer. Issue 10 (13th November 2018) - Johnson, Stephanie; Butow, Phyllis; Bell, Melanie; Detering, Karen; Clayton, Josephine; Silvester, William; Kiely, Belinda; Clarke, Stephen; Vaccaro, Lisa; Stockler, Martin; Beale, Phillip; Fitzgerald, Natalie; et al.
Abstract Background We modified and evaluated an advance care planning (ACP) intervention, which had been shown to improve compliance with patient's end of life (EoL) wishes, in a different patient population. Methods Patients with incurable cancer, and a Family Member (FM), were randomised one-to-one to usual care or usual care plus an ACP intervention, between April 2014 and January 2017. Oncologists and participants were non-blinded. ACP was based on the Respecting Patient Choices model, with an offer to provide individualised ranges for typical, best-case and worst-case scenarios for survival time. Seven facilitators (two oncology nurses, two nurses and three allied health professionals) delivered the intervention within 2 weeks of study enrolment. The primary outcome measure, assessed by interviewing the FM 3 months after patient death, was the FM perception that the patient's wishes were discussed, and met. Results Six hundred and sixty-five patients from seven Australian metropolitan oncology centres were referred for consideration by their oncologists, 444 (67%) met the study inclusion criteria and were approached by a study researcher. Two hundred and eight patients (47%) and their FM entered the trial as dyads. Fifty-three (46%) dyads in the ACP group and 63 (54%) dyads in the usual-care group had complete primary outcome data (p  = 0.16). Seventy-nine patients and 53 FMs attended an ACP discussion. Mean length of discussion was 57 min. FMs from 23 (43%) dyads allocated to ACP and 21 (33%) dyads allocated usual care reported the patient's EoL wishes were discussed and met (difference 10%, 95% CI: −2 to 8, p  = 0.27). There were no differences in EoL care received, patient satisfaction with care; FM satisfaction with care or with death; or FM well being. Rates of palliative care referral were high in both groups (97% vs 96%). Conclusions A formal ACP intervention did not increase the likelihood that EoL care was consistent with patients' preferences.